2006
DOI: 10.2478/s11756-006-0058-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 864 MHz electromagnetic field on growth kinetics of established cell line

Abstract: Considering often contradictory data on biological effects of mobile phones frequencies on established cell culture lines, our study aimed at evaluating the influence of 864 MHz electromagnetic field on proliferation, colony forming ability and viability of Chinese hamster lung cells continuous line V79. Prior to exposure for 1, 2 and 3 hours in transversal electromagnetic mode cell (TEM-cell) equipped by Philips PM 5508 signal generator cell samples were sub-cultivated for one day. Cell samples were exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Also in studies on animal cells, significant changes in proliferation were found after electromagnetic field exposure. Pavicic and Trosic [42] observed a decrease in the proliferation of Chinese hamster lung cells exposed to 864 MHz. Zhu et al [43] showed that microwaves emitted by mobile phones lead to a significant reduction in the survival of in vitro cultured rat cortical neuronal cells.…”
Section: Discussionmentioning
confidence: 98%
“…Also in studies on animal cells, significant changes in proliferation were found after electromagnetic field exposure. Pavicic and Trosic [42] observed a decrease in the proliferation of Chinese hamster lung cells exposed to 864 MHz. Zhu et al [43] showed that microwaves emitted by mobile phones lead to a significant reduction in the survival of in vitro cultured rat cortical neuronal cells.…”
Section: Discussionmentioning
confidence: 98%
“…Literaturni podaci o istra`ivanjima in vitro obuhva}aju {irok raspon stani~nih pokazatelja koje su istra`iva~i pratili nakon izlaganja kultura kontroliranim uvjetima zra~enja. Pokazano je da izlaganje stanica trajne kulture frekvencijama mobilne telefonije utje~e na kinetiku rasta stanica ovisno o duljini zra~enja te mo`e uzrokovati strukturne promjene na razini genskog materijala (34,35). Nalazi, pak, koje je objavila skupina istra`iva~a iz 2001. god.…”
Section: Stadiji U Procesu Spermatogenezeunclassified
“…We tested this assumption by exposing a continuous V79 cell line to an 864 MHz continuous wave at an average SAR of 0.08 W kg -1 under strictly controlled experimental conditions. Irradiation significantly affected cell proliferation but not viability or colonyforming ability (33).…”
Section: Cellular Biomarkers Of Rf/mw Exposurementioning
confidence: 99%